Gender Imbalance and The Nigeria’s Democratizing Process - Jibril, Abubakar; Kawuwa, Suleiman (School of Social Sciences, USM, 2017)
This paper attempts to analyse the gender imbalance existing in the Nigeria’s democratizing process. Gender imbalance has been a permanent feature in the democratic politics of most countries of the world, including Nigeria, with women being relegated to the background. Thus, women remain the marginalised gender. This marginalisation, the paper argued, is partly derived from the pattern of socialisation of men and women into the different roles in the society and which subsequently results in unequal access to and unfair distribution of resources. This impedes development and productivity. Various attempts were made by the international community and national governments to address this problem. However, in spite of these efforts, the representation of women in the Nigerian democratising process, even though could be said to have relatively improved, is still very low. This is because the female gender in Nigeria, often, are besieged with many challenges which militate against their effective participation in the country’s democratic process and the continued male dominance in this area of human endeavour. These challenges, as discussed in the work, include among others, the patriarchal ideology, money politics, illiteracy and the general nature of the country’s political terrain. Based on the foregoing, some recommendations were made such as intensifying efforts on gender affirmative actions, need for the ratification of protocols and treaties on gender equality to which Nigeria is a signatory, change in our attitudes, among other things.